PENGGUNAAN RAD MODEL DALAM PERANCANGAN SISTEM INFORMASI PENERIMAAN MAHASISWA BARU STKIP MUHAMMADIYAH MUARA BUNGO - Yogi Irdes Putra; Rini Sefriani; Ahmad Ridoh; Raja Bani Pilitan; Ade Kurniawan (Jurnal Inovasi Pendidikan dan Teknologi Informasi (JIPTI), 2021)
The purpose of this research is to produce a new admissions information system that is eligible for registration of prospective students. This research uses RAD model (Rapid Application Development) method. The research stages include requirements planning, design, and implementation. The new student admission information system that has been designed to provide convenience to prospective new students to register at STKIP Muhammadiyah Muara Bungo.